Guiding underprepared students to success in higher education - McCall, Alyson (Kansas State University, 2014)
Students are entering institutions across the country unprepared to meet the demands of higher education. While Kansas is above the national average for students prepared for higher education, only twenty-nine percent of Kansas seniors are considered "prepared” for college in the four determined benchmark areas, compared to the twenty-five percent national average (ACT, 2012). With this statistic, ACT indicates that only one fourth of students complete high school requirements in such a way that leads to success post-graduation. Students are not ready for the expectations of higher education, and as a result this population is less likely to succeed. Further, development opportunities targeted at underprepared students are largely unsuccessful at reaching the population. This report looks at the unprepared student population, the role of higher education, and the projected future for underprepared students in higher education. In an effort to encourage holistic development and successful support initiatives, recommendations for higher education practices and research are discussed.
Keywords: Higher education; Underprepared students; College readiness; Higher Education (0745)